Pengembangan Media Pembelajaran XyMath Berbasis Inventor 2 pada Materi Sistem Persamaan Linear Dua Variabel Kelas VIII - Rezkianti Hasan; Nurkholis; Sri Sulasteri (Alauddin Journal of Mathematics Education, 2022)
This study aims to determine the process of developing mathematics learning media for two-variable linear equation systems in MTs Darul Falah Bikeru that meet valid, practical, and effective criteria. This research is in the form of Research and Development (R&D) research with the ADDIE development model. The procedure includes 5 stages, namely: (1) analysis stage, (2) design stage, (3) development stage, (4) implementation stage, (5) evaluate stage. The subject of this study was class VIII students at MTs Darul Falah Bikeru. The product that was successfully developed in this development is the XyMath application created using Inventor 2. The results of this study show that the development of Inventor 2-based XyMath learning media on the material of the Two-Variable Linear Equation System is feasible to use in MTs Darul Falah Bikeru. From the results of product trials, students are more interested and understand the material taught using XyMath learning media compared to using digital books